1997
DOI: 10.1148/radiology.205.2.9356612
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysm: anatomic factors that predict the usefulness of intraoperative angiography.

Abstract: The rate of clip repositioning in aneurysms of the posterior communicating or anterior choroidal arteries was less than that at other locations (P < .05). Intraoperative angiography may not be necessary when aneurysms are at these two locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 7 publications
1
19
1
3
Order By: Relevance
“…Derdeyn et al 11 ., also demonstrated that the frequency of clip adjustment is associated with the size and location of the aneurysm. In their series, intraoperative angiography prompted clip adjustment in 46 (16.8%) of 273 patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Derdeyn et al 11 ., also demonstrated that the frequency of clip adjustment is associated with the size and location of the aneurysm. In their series, intraoperative angiography prompted clip adjustment in 46 (16.8%) of 273 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the delay in obtaining information about blood flow may be unacceptable and the complication rate of angiography is by no means negligeble (1.7 to 2.9%) 8,9 . Nevertheless, several studies have documented the rates of vessel occlusion or clip adjustment based on angiographic findings [5][6][7]10,11 . In a series of 66 patients who underwent postoperative angiography, Macdonald et al 5 reported that there were unexpected stenosis in nine out of 78 (11.5%) patients, resulting in six strokes and two deaths (10.3%).…”
Section: Discussionmentioning
confidence: 99%
“…5,8,14,15,17,23,25,27,31) The size and location of the aneurysm are correlated with the need to reposition the aneurysm clip after intraoperative angiography. 1,7,22) The subgroup of patients with giant or large aneurysm, and basilar apex, posterior communicating artery, or superior hypophyseal artery aneurysms had a significantly higher incidence of clip adjustment. 1,7,22) Although our study found that aneurysm location appeared to have no effect on the rate of clip repositioning, the rate of clip adjustment increased significantly with Intraoperative Angiography for Unruptured Aneurysms increasing aneurysm size.…”
Section: Discussionmentioning
confidence: 98%
“…Intraoperative angiography has been used in the surgical treatment of cerebral aneurysms in various series, including ours, consisting of 1073 aneurysms (Table 3). [1][2][3]6,7,9,11,16,17,19,21,22,28,32) Clip adjustment was performed in 13.8% of cases: residual aneurysms and arterial (Table 4). 5,8,14,15,17,23,25,27,31) The size and location of the aneurysm are correlated with the need to reposition the aneurysm clip after intraoperative angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation